EXPLORING THE POTENTIAL OF VIRTUAL REALITY AS A TOOL FOR ENHANCING CLIMATE CHANGE AWARENESS: A REVIEW - Saad Akbar,; Jaweria Imran,; Humera Azam,; Mohammad Ayub Latif,; Aqsa Nadir, (Spectrum of Engineering Sciences, 2025)
Climate change is one of the biggest social, cultural, environmental and economic issue we face in modern society which takes solutions from everyone at every level. Regular climate education rarely meets the complexity and fear of climate change with its trauma-informed methods. Researchers have explored the use of Virtual Reality (VR) as a tool to enhance climate change literacy. VR is an asset allowing us to visualize realistic situations and under-stand what happens in climate change, reinforcing our emotional response. It also gives them a better insight into distant environmental issues. Based on an analysis of several studies, VR is examined as a possible educational resource to increase climate change literacy. Being that VR platforms can be anything from high-end headsets to low-cost devices, their availability empowers educators with the ability to target a broad audience. The only way one gets an interface to be both meaningful and enjoyable, is by improving renderings, controls responsiveness, and user experience. Until the expansion and subtle integration of VR into education systems, VR might be the best tool we have to raise environmental awareness and inspire sustainable actions for future generations.